Epicardium-derived fibroblasts in heart development and disease - Fang, Ming (J Mol Cell Cardiol, 2015)
The majority of cardiac fibroblasts in a mature mammalian heart are derived from the epicardium during prenatal development and reactivate developmental programs during the progression of fibrotic disease. In addition, epicardial activation, proliferation, and fibrosis occur with ischemic, but not hypertensive injury. Here we review cellular and molecular mechanisms that control epicardium-derived cell lineages during development and disease with a focus on cardiac fibroblasts. This article is part of a special issue entitled “Fibrosis and Myocardial Remodeling”.